2023
DOI: 10.1109/tie.2022.3165300
|View full text |Cite
|
Sign up to set email alerts
|

Three-Phase Inverter Fed Adjustable Field IPMSM Drive Utilizing Zero-Sequence Current

Abstract: This article proposes a three-phase four-wire inverter drive system for an adjustable field interior permanent magnet synchronous motor utilizing magnetic saturation. The magnetic saturation is regarded as a phenomenon of a decrease in permeability depending on an extra magnetic field. In the proposed motor, the number of flux linkage can be controlled by modulating the permeability of magnetic leakage paths in the rotor. However, the proposed adjustable field method requires an additional magnetomotive force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As a result, it has been revealed that the proposed drive circuit is more straightforward and efficient in terms of system volume and switching loss than the conventional adjustable field PMSM drive system. In addition, the references [13] and [14] revealed that the proposed adjustable field method could achieve field control with lower copper loss and harmonics than the conventional field weakening control [15]- [19].…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…As a result, it has been revealed that the proposed drive circuit is more straightforward and efficient in terms of system volume and switching loss than the conventional adjustable field PMSM drive system. In addition, the references [13] and [14] revealed that the proposed adjustable field method could achieve field control with lower copper loss and harmonics than the conventional field weakening control [15]- [19].…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, adjustable field PMSMs have been widely researched for driving range expansion [1]- [12]. The authors also have studied the adjustable field IPMSM focusing on the magnetic saturation of a soft magnetic material [13] and [14]. We call the motor the adjustable field IPMSM based on permeability modulation because the motor can control the magnetic field while modulating the permeability of the magnetic leakage paths between PMs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations